Case–Control Study of Human Papillomavirus and Oropharyngeal Cancer - D'Souza, Gypsyamber; Kreimer, Aimee R; Viscidi, Raphael; Pawlita, Michael; Fakhry, Carole; Koch, Wayne M; Westra, William H; Gillison, Maura L (The New England journal of medicine, 2007)
This study offers persuasive evidence of a strong association between exposure to or oral infection with the human papillomavirus and oropharyngeal cancer. The data indicate that sexual behaviors can spread the virus to the oral cavity. The use of tobacco, alcohol, or both did not strengthen the association between exposure to HPV and oropharyngeal cancer. Among patients who had no evidence of exposure to HPV, however, tobacco and alcohol use were strongly associated with oropharyngeal cancer. This study offers persuasive evidence of a strong association between exposure to or oral infection with HPV and oropharyngeal cancer. The use of tobacco, alcohol, or both did not strengthen the association between exposure to HPV and oropharyngeal cancer. Infection with sexually transmitted human papillomavirus (HPV) is a cause of virtually all cervical cancers. 1 Molecular evidence also provides support for a role for HPV, particularly HPV-16, in the pathogenesis of a subgroup of squamous-cell carcinomas of the head and neck. 2 Genomic DNA of oncogenic HPV is detected in approximately 26% of all squamous-cell carcinomas of the head and neck worldwide, 3 but the molecular evidence is most rigorous and consistent for oropharyngeal squamous-cell carcinoma, in which viral integration and the expression of viral oncogenes (E6 and E7) have been shown. 4 The epidemiologic evidence of a causal role for HPV in . . .